Monitoring of Bacillus spore-forming dynamics through flow cytometry - Chen, Zhili; Lu, Yuanyuan; Cui, Jiazhen; Feng, Yuzhong; Dong, Haolong; Huang, Xuan; Zhu, Chen; Xiong, Xianghua; Chen, Huipeng; Wang, Qingyang; Liu, Gang (Frontiers in Microbiology, 2024)
The plate counting method is a traditional and widely accepted technique for live cell counting, often employed for Bacillus enumeration and spore forming rate calculations. However, this method requires at least 12 h to generate results, making it unsuitable for real-time monitoring of bacterial growth status and spore transformation rate. Bacillus thuringiensis crystals, produced during sporulation, are widely used as microbial pesticides, with high demand for industrial scale production. Variations in cultivation conditions and harvest timing during large-scale pore production of Bacillus thuringiensis significantly affect spore forming rate, impacting crystallization yield. Nevertheless, there is a lack of real-time monitoring methods for spore conversion rate. Flow cytometry (FCM), a well-established technique for single-cell analysis in eukaryotic cells, has been successfully applied in bacterial detection in environmental and food samples. In this study, we introduced a rapid flow cytometry-based method for determining spore forming rate of Bacillus thuringiensis, with two nucleic acid dyes, SYTO24 and LDS751. The method enables dynamic monitoring of spore, vegetative cell, and viable but non-culturable/dead cell proportions during the whole cultivation process, and spore forming rate could be gained within 30 min. Data of spore forming rate by FCM method is consistent with that by plate counting method, offering a faster and more efficient approach for assessing sporulation status in industrial Bacillus thuringiensis microbial pesticide production.